Risk factors for gastrointestinal perforation and anastomotic leak in patients submitted to cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) - Nogueiro, Jorge; Nik Qisti Fathi; Guaglio, Marcello; Baratti, Dario; Kusamura, Shigeki; Deraco, Marcello (Elsevier, 2023)
Background: Gastrointestinal leak is one of the most feared complications after cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) and harbors significant postoperative morbidity and mortality. We aim to identify risk-factors for anastomotic leak (AL) and gastrointestinal perforation (GP) to optimize postoperative outcomes of this population. Methods: We performed a retrospective analysis of 1043 consecutive patients submitted to CRS in a single institution. Potential risk factors for AL and GP, both related to patient overall condition, disease status and surgical technique were reviewed. Results: Anastomotic leaks were identified in 5.2% of patients, and GPs in 7.0%. The independent risk-factors for AL were age at surgery (OR1.40; CI95% 1.10–1.79); peritoneal cancer index (PCI) (OR1.04, CI95% 1.01–1.07); Cisplatin dose >240 mg during HIPEC (OR3.53; CI95% 1.47–8.56) and the presence of colorectal (CR) or colo-colic (CC) anastomosis (OR5.09; CI95% 2.71–9.53, and 4.58; CI95% 1.22–17.24 respectively). Male gender and intraoperative red blood cell transfusions were the only independent risk factors for GP identified (OR1.70; CI95% 1.04–2.78 and 1.06; CI95% 1.01–1.12, respectively). Regarding 30-day and 90-day postoperative mortality, independent risk-factors were mainly related to patient's overall condition. Conclusion: Gastrointestinal leaks are a frequent source of postoperative morbidity, mainly at the expense of GP. A careful and systematic intraoperative revision of all potential gastrointestinal injuries is equally critical to perfecting anastomotic fashioning techniques to decrease gastrointestinal complication rates. We identified multiple risk-factors for AL and GP related to disease status and patient condition. Our study suggests that patient-related conditions are of paramount relevance, highlighting the importance of patient selection and preoperative patient optimization.